Assessment Of Maturity Status Of E-Government Websites In Malaysia Through Website Content Analysis - Eskandar, Aria Asadi (2010)
This study aimed to assess and evaluate maturity status of e-Government in Malaysia (at state level) according to e-Government system which citizens interact with. Transparency, interactivity, usability/accessibility, citizen partizipation, privacy/security, and service maturity were selected as the main dimensions and performance measures for assessment and evaluation of e-Government web portals.